Revolutionizing the sciences : European knowledge and its ambitions, 1500-1700 - Dear, Peter, 1958- (Princeton, N.J. : Princeton University Press, 2001)
"This is an ideal textbook on the Scientific Revolution for courses on the history of science or the history of early modern Europe. The text is chronologically arranged and fully covers both the sixteenth and seventeenth centuries, standing alone as an up-to-date, complete general introduction to the origins of modern science in Europe." "Revolutionizing the Sciences is the best available choice for teaching or learning about the developments that came to be called the Scientific Revolution."--Jacket.
Introduction: Philosophy and operationalism -- "What was worth knowing" in 1500 -- Humanism and ancient wisdom: how to learn things in the sixteenth century -- The scholar and the craftsman: Paracelsus, Gilbert, Bacon -- Mathematics challenges philosophy: Galileo, Kepler, and the surveyors -- Mechanism: descartes builds a universe -- Extra-curricular activities: new homes for natural knowledge -- Experiment: how to learn things about nature in the seventeenth century -- Cartesians and Newtonians -- Conclusion: What was worth knowing by the eighteenth century?
Includes bibliographical references and index.
Keywords: Science -- Europe -- History